The Effect Of Kersen (Muntingia calabura) Extract On The Number Of Pancreatic Beta Cells: Experiment Study In Rat - Muthmainah S.P, Sri Mega; Romdhoni, Muhammad Fadhol; Ningrom, Ira Citra; Annisa, Yunia (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Type 2 diabetes mellitus is a common type of diabetes which can be caused by an increase in blood sugar levels resulting in a decrease in the number of pancreatic beta cells, dysfunction or apoptosis. To increase the number of pancreatic beta cells, antioxidants are needed. The antioxidant content of kersen leaves can improve pancreatic beta cell disorders due to high blood sugar levels by reducing ROS and RNF so that oxidative stress decreases and the number of pancreatic beta cells increases. Aim of this research, to determine the effect and the most effective dose of kersen leaves ethanol extract on the number of pancreatic beta cells of white rats wistar strain induced by streptozotocin-nicotinamide (STZ-NA). This study used a true experiment post-test only with control group design with STZ-NA-induced KI-KV group and normal control KVI group. KI-KIII was given kersen leaves extract at a dose of 0.3; 0.5 ;0.7 mg/gBW. KIV positive control. KV negative control. At the end of the study, the pancreas of rats was made preparations with immunohistochemical staining and the average pancreatic beta cells from the 5 islets of Langerhans were calculated. The average number of pancreatic beta cells that were most effective from the kersen leaves treatment group was KI (dose of 0.3 mg/gBW) with an average of 39.9. There is an effect of ethanol extract of kersen leaves on increasing the number of pancreatic beta cells in white rats of wistar strain induced by STZ-NA with an effective dose of 0.3 mg/gBW.